Ion Transport Mechanism in Flexible PMMAIL/LiTf Films - Akemal Muhd Zailani, Nabilah; Abdul Latif, Famiza; Malik Marwan Ali, Ab; Azri Ab Rani, Mohd A; Zu Azhan Yahya, Muhd (International Journal of Engineering and Technology, 2019)
Acrylates such as poly (methyl methacrylate) (PMMA) has been widely studied as polymer electrolyte film due to its good mechanical stability towards lithium electrode.  However, commercial PMMAs even at high molecular weight are not able to produce flexible films due to their polar nature that prone to form interchain crosslinking via hydrogen bonding. Therefore, the formation of hydrogen bonding was hindered by incarcerating ionic liquid (IL) of 1-methyl-3-pentamethyldisiloxymethylimidazolium bis(trifluoromethylsulfonyl)imide, [(SiOSi)C1C1im] [NTf2] during free radical polymerization of MMA. Interestingly, the synthesized PMMA containing IL (PMMAIL) produced flexible and free standing films with ionic conductivity of ~10-7 S cm-1. Though the ionic conductivity obtained is comparable with other doped PMMA film electrolytes that had been studied, it is still considered as low for application in energy storage devices. As an alternative, in this study, lithium triflate (LiTf) salt was added into the PMMAIL system and the highest ionic conductivity obtained was 2.65 ×10-4 S cm-1 with addition of 30 wt.% LiTf at ambient temperature. The temperature dependence conductivity and AC conductivity behaviour of PMMAIL/LiTf were further investigated in order to fully understand the ion transport mechanism that occurred in the system. It was found that the PMMAIL/LiTf system fits the Arrhenius behaviour and Correlated Barrier Hopping (CBH) model.